Application and Assessment of an Ethics Presentation for Accounting and Business Classes - Smith, L. Murphy (Journal of business ethics, 2005)
This paper describes a presentation on ethics for accounting and business students. In 2001 and 2002, major corporate failures such as Enron and Worldcom, combined with questionable accounting practices, made ethics a paramount concern to persons working in business and accounting. While financial statement analysis and regulatory requirements are important technical topics, the issue of ethics provides faculty a unique and very appropriate setting to discuss deeper truths about doing business and living life well. This paper briefly describes the development and assessment of one approach to presenting ethics built around a computerized slide show (PowerPoint). The goal of the presentation is to increase students’ understanding of the essential role of ethics to accounting and business. Following the presentation, students indicated a heightened recognition of the importance of ethics. Educators should do all that they can to encourage students to do the “right” thing, even in difficult circumstances. This encouragement may serve them well in school and later in their careers.